2019
DOI: 10.1177/2165079918813380
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Related Illness in Midwestern Hispanic Farmworkers: A Descriptive Analysis of Hydration Status and Reported Symptoms

Abstract: Heat-related illness (HRI) is a largely undocumented phenomenon in Midwestern Hispanic migrant and seasonal farmworkers in the United States. Frequently, the physiological burden of crop production is overlooked while workers are in the fields. We completed a mixed-methods study using a cross-sectional survey among migrant and seasonal farmworkers about their experience with HRI symptoms (N = 148) and conducted an intensive surveillance on a smaller group of workers (N = 20) in field trials (N = 57 trials) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 52 publications
(57 reference statements)
1
26
0
Order By: Relevance
“…This finding is also supported by a study conducted across countries. Which stated that uninterrupted strenuous job in a hot environment with a very few rest periods and lack of potable water contributes to a high incidence of heatstroke, heat exhaustion and heat cramps among farm workers [5,9,20,21,37,38]. Another study also reported that farm workers are four times more likely to experience HRI than other industries workers as a result of high ambient temperatures [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also supported by a study conducted across countries. Which stated that uninterrupted strenuous job in a hot environment with a very few rest periods and lack of potable water contributes to a high incidence of heatstroke, heat exhaustion and heat cramps among farm workers [5,9,20,21,37,38]. Another study also reported that farm workers are four times more likely to experience HRI than other industries workers as a result of high ambient temperatures [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher risk of mental health problems [9,13], acute and chronic pesticide poisoning [9,18] and heat-related illness [5,7,[19][20][21][22] were reported among migrant and seasonal farm workers. However, underreporting of medical conditions is significant due to limited access to health services, and fear of lost wages or jobs [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Culp and Tonelli et al (2019) conducted a study on heat stress exposure using wearable devices. Their research focused on agricultural workers’ physiological responses during agricultural work and linked them to working intensity and climate conditions (measured by the WBGT) [ 28 ]. The authors discovered considerably higher body temperatures, increased hr, and respiration rate in the uncomfortable intensity category.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, HRI involves complex interactions between environmental heat strain, clothing, and human thermal physiology 21 . Recently, a wearable sensor for monitoring workers’ conditions has been developed 22 . US NIOSH recommends physiologic monitoring such as heart rate and/or core temperature of heat-exposed workers 16 .…”
Section: Introductionmentioning
confidence: 99%